A atitude leitora dos pais e sua relação com a formação do leitor iniciante - Silva, Nanci Madalena Amaro da [UNESP] (2015)
The research The reader attitude of parents and its relationship with the formation of the beginning reader aimed to explain the relationships that may exist between the reader attitude of parents and the reading learning process by children in the first year of elementary school. And it has as its specific objectives: to verify whether parents or other adults perform reading practices for themselves and/or to the children at home; identify reading materials available in the family environment for the realization of reading practices; check if the children have access to reading materials available in the family environment; see if their parents or other adult help children in their reading tasks; and correlate the grade of facility of the child in learning to the reader attitude of parents or adults who live in the house. The study was conducted through qualitative research, using the following data collection instruments: observations of students in the classroom and interviews with students and their parents or adults with whom they live. The research was conducted in a State School of Marilia, in which the researcher is the teacher of the research subjects. The research results, based on interviews with parents and children and on the observation in the classroom of the children acts of reading, were analyzed with support in the following categories parents and the act of reading, reading materials in the house and at school, children and the act of reading and influence of the reader attitude of parents on the children learning of reading. Test results indicate that there is a relationship between the reader attitude of the parents and the child's learning, i.e., the child has more facility in learning to read when parents or adults with whom he/she lives in the house not only give him/her reading materials, but are dedicated to read for themselves, with him/her and for him/her.